Juegos tradicionales en la integración social de niños de 7 a 8 años. - Cayambe Jaya, Jhonatan Rubén (2024)
The general objective of this research was to determine whether traditional games promote social integration in third-grade children from the Simón Rodríguez Educational Unit. Theoretically, traditional games are considered to represent a resource of great educational value in themselves, which contributes to the physical, emotional and sociocultural development of the child. On the other hand, they are actions that occur through contact between two or more people outside their family nucleus. Methodologically, a mixed approach was used, with a quasi-experimental, transversal and field design. The population was made up of third-grade students, the sampling was non-probabilistic and intentional, the technique was the psychometric test and the instrument was the Social Interaction Skills Questionnaire (CHIS; Monjas, 1992). Based on the parametric statistical test T student for paired differences pre and post, where a bilateral significance level of 0.00 can be observed, obtaining a result P value = < 0.01 with a very significant bilateral significance level, demonstrating that the intervention plan for traditional games favors the development of students' social interaction. Based on the development of the pre-test and post-test, it was possible to identify the importance of developing a traditional games intervention program as they improved social integration, allowing students to develop cooperative and individual activities, favoring their integral, social, emotional and academic well-being.